Out of Nature: Why Drugs from Plants Matter to the Future of Humanity - Gremillion, Kris (Ethnobiology Letters, 2013)
Review of Out of Nature: Why Drugs from Plants Matter to the Future of Humanity. Kara Rogers. 2012. The University of Arizona Press, Tucson. Pp. 216. 19.95 (paper). ISBN 978-0-8165-2969-8.